(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the quality of life of children born prematurely at preschool age. The participants were 15 children, 09 born prematurely and 06 at term, of both sexes, aged between four and six years. The children assessed themselves using the instrument Autoquestionnaire Qualité by Vie Enfant Imagé, with the help of figures and faces that express different emotional states and the scores differ respectively from very unhappy, unhappy, happy and very happy. Of the 15 children evaluated, 60.0% were born prematurely, 40% were born at term, and 13.3% had questionable neuropsychomotor development at the time of self-assessment. The mean quality of life score of the sample was 52.3, on a scale from zero to 78, with a standard deviation of 8.7, a minimum of 35 and a maximum of 65. Children feel happier on their birthday ( 80.0%), at the table with the family (80.0%), when they think of their father (73.3%), when they watch television (73.3%), when they are with their grandparents (66.7% ), when they see their own photograph (66.7%), when they think about growing up (66.7%), when they think about their mother (60.0%), during vacations (60.0%), at night when they go to bed (60.0%), in playtime, during school recess (60.0%), when they do their homework (60.0%), when friends talk to them (53.3% ), when the father or mother talks to them (53.3%). There was no significant difference between genders, ages, prematurity or not, and neuropsychomotor development in terms of quality of life score (p>0.05).